Modification of Bacteriophages to Increase Their Association with Lung Epithelium Cells In Vitro - Aurelija M. Grigonyte; Alexia Hapeshi; Chrystala Constantinidou; Andrew Millard (MDPI AG, 2021)
There is currently a renaissance in research on bacteriophages as alternatives to antibiotics. Phage specificity to their bacterial host, in addition to a plethora of other advantages, makes them ideal candidates for a broad range of applications, including bacterial detection, drug delivery, and phage therapy in particular. One issue obstructing phage efficiency in phage therapy settings is their poor localization to the site of infection in the human body. Here, we engineered phage T7 with lung tissue targeting homing peptides. We then used in vitro studies to demonstrate that the engineered T7 phages had a more significant association with the lung epithelium cells than wild-type T7. In addition, we showed that, in general, there was a trend of increased association of engineered phages with the lung epithelium cells but not mouse fibroblast cells, allowing for targeted tissue specificity. These results indicate that appending phages with homing peptides would potentially allow for greater phage concentrations and greater efficacy at the infection site.